Alih Teknologi Diversifikasi Berbasis Nanas sebagai Produk Unggulan Desa Karangjengkol dan Rintisan Ekowisata Kawasan Hutan dengan Tujuan Khusus (KHDTK) - Purbowati, Ike Sitoresmi Mulyo; Maksum, Ali; Wijonarko, Gunawan (Jurnal Ilmiah Pangabdhi, 2025)
The productivity of pineapple in Karangjengkol Village, Purbalingga Regency is 110 million/Ha/year. Based on the situation analysis, currently pineapple sales use the slashing system and the existing processed products are jam, jam and pineapple dodol with low quality. As a result, the price obtained is low and the shelf life of pineapple and its processed products is relatively short, which is 3 days for fresh pineapple and 14 days for its processed products. The objectives of this community service are: 1) To find out the understanding and implementation of pineapple dodol and instant powder processing techniques. 2) To find out the level of mastery of target group members regarding simple post-harvest technology, namely grading, coating harvest wounds with rosella antimicrobial bioactive compounds. After the technology transfer, the increase in the number of people who know the proper and correct processing methods regarding dodol, instant powder and grading increased, respectively: 17%, 22% and 34%. Grading and rinsing wounds with rosella extract disinfectant can prevent contaminants and extend the shelf life of fresh pineapple. In the manufacture of instant powder, stirring after caramelization and stopping the heat source must be done quickly and without pause until small crystals are formed. In the processing of dodol, the right stirring and temperature affect the quality attributes of the resulting dodol.